2022
DOI: 10.14336/ad.2022.1206
|View full text |Cite
|
Sign up to set email alerts
|

Higher Functional Connectivity of Ventral Attention and Visual Network to Maintain Cognitive Performance in White Matter Hyperintensity

Abstract: Ventral attention network (VAN), associated with cognitive performance, is one of the functional networks that are most vulnerable in white matter hyperintensity (WMH). Considering the global interaction of networks for cognitive performance, we hypothesized that VAN-related between-network connectivity might play a role in maintaining cognition in patients with WMH. We included 139 participants for both cross-sectional and longitudinal analysis from CIRCLE study (ClinicalTrials.gov ID: NCT03542734) between Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…However our results refer to a different spatial scale and, come from a static analysis, are not expected to be fully reproducing with the results in ( Luppi et al, 2022 ): notice that the emergence of a synergistic circuit made of visual, somatomotor and ventral attention has not been observed in previous studies. We remark that in a recent paper it has been observed that ventral attention and motor network connectivity are relevant to functional impairment in spatial neglect after right brain stroke ( Barrett et al, 2019 ); moreover higher functional connectivity of ventral attention and visual network has been found to play a role to maintain cognitive performance in white matter hyperintensity ( Zhu et al, 2023 ). These findings renders even more interesting our results, i.e., these three networks belonging to a synergistic informational circuit in the resting brain.…”
Section: Discussionmentioning
confidence: 88%
“…However our results refer to a different spatial scale and, come from a static analysis, are not expected to be fully reproducing with the results in ( Luppi et al, 2022 ): notice that the emergence of a synergistic circuit made of visual, somatomotor and ventral attention has not been observed in previous studies. We remark that in a recent paper it has been observed that ventral attention and motor network connectivity are relevant to functional impairment in spatial neglect after right brain stroke ( Barrett et al, 2019 ); moreover higher functional connectivity of ventral attention and visual network has been found to play a role to maintain cognitive performance in white matter hyperintensity ( Zhu et al, 2023 ). These findings renders even more interesting our results, i.e., these three networks belonging to a synergistic informational circuit in the resting brain.…”
Section: Discussionmentioning
confidence: 88%